2018
DOI: 10.3389/fimmu.2018.00192
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Sporozoites of Plasmodium berghei Effectively Activate Liver CD8α+ Dendritic Cells

Abstract: Immunization with radiation-attenuated sporozoites (RAS) shown to confer complete sterile protection against Plasmodia liver-stage (LS) infection that lasts about 6 to 9 months in mice. We have found that the intermittent infectious sporozoite challenge to immune mice following RAS vaccination extends the longevity of sterile protection by maintaining CD8+ T cell memory responses to LS infection. It is reported that CD8α+ dendritic cells (DCs) are involved in the induction of LS-specific CD8+ T cells following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…The increasing involvement of the hepatic CD8 + T cell response might be supported by continuously accumulating, activated dendritic cells at the site of infection, as shown to occur in the course of i.v. RAS immunizations and other infection models ( 23 , 36 40 ). Enhanced frequencies of antigen-presenting cells (APC) in the liver might promote the reactivation and build-up of local hepatic CD8 + T cell populations during vaccine-induced secondary and tertiary responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing involvement of the hepatic CD8 + T cell response might be supported by continuously accumulating, activated dendritic cells at the site of infection, as shown to occur in the course of i.v. RAS immunizations and other infection models ( 23 , 36 40 ). Enhanced frequencies of antigen-presenting cells (APC) in the liver might promote the reactivation and build-up of local hepatic CD8 + T cell populations during vaccine-induced secondary and tertiary responses.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent study reported that the accumulation and activation status of intrahepatic CD8α + DC was significantly increased by i.v. injection of a higher compared to a lower Pb RAS dose ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liver cells including hepatocytes, liver sinusoidal endothelial cells, Kupffer cells, hepatic DCs and hepatic stellate cells interact with the parasite during the liver invasion process (as reviewed by Hafalla et al 81 ). Rodent studies have shown that CD11c + DCs found in the spleen, liver and liver‐draining lymph nodes are required to present antigens to CD8 + T cells, and their depletion abrogates CD8 + T‐cell responses 5,82‐84 . It is thought that these DCs directly present sporozoite antigens to CD8 + T cells through antigen cross‐presentation 5,8,83 .…”
Section: Immune Responses To Malaria Pre‐erythrocytic Stages In the Smentioning
confidence: 99%
“…Rodent studies have shown that CD11c + DCs found in the spleen, liver and liver‐draining lymph nodes are required to present antigens to CD8 + T cells, and their depletion abrogates CD8 + T‐cell responses 5,82‐84 . It is thought that these DCs directly present sporozoite antigens to CD8 + T cells through antigen cross‐presentation 5,8,83 . Blocking the ability of the DCs to cross‐present antigens represses CD8 + T‐cell responses 85,86 .…”
Section: Immune Responses To Malaria Pre‐erythrocytic Stages In the Smentioning
confidence: 99%
See 1 more Smart Citation